2018
DOI: 10.1108/ijhma-03-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal neighbourhood-level house price index

Abstract: Purpose-The purpose of this study is to develop a spatio-temporal neighbourhood-level house price index (STNL-HPI) incorporating a geographic information system (GIS) functionality that can be used to improve the house price indexation system. Design/methodology/approach-By using the Malaysian house price index (MHPI) and application of geographically weighted regression (GWR), GIS-based analysis of STNL-HPI through an application called LHPI Viewer v.1.0.0, the stand-alone GIS-statistical application for STNL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…Apart from that, the land size shows a positive coefficient because investors or buyers are willing to pay a higher price to occupy a larger space in accordance with the theory of economic utility. The geocoded variables (latitude and longitude) are significant, which agrees with the past studies (Clapp 2004;Nappi-Choulet and Maury 2009;Helbich et al 2013;Sipan et al 2018). Therefore, the existence of price variability of heritage properties at the local level is proved to be significant in this study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Apart from that, the land size shows a positive coefficient because investors or buyers are willing to pay a higher price to occupy a larger space in accordance with the theory of economic utility. The geocoded variables (latitude and longitude) are significant, which agrees with the past studies (Clapp 2004;Nappi-Choulet and Maury 2009;Helbich et al 2013;Sipan et al 2018). Therefore, the existence of price variability of heritage properties at the local level is proved to be significant in this study.…”
Section: Resultssupporting
confidence: 91%
“…It gives the quality-adjusted price change between the base period 0 and each comparison period t. The HTDRM also integrates with the coordinates of the property (latitude and longitude) in order to capture the variability of the property price due to the location (Clapp 2004). There are a few studies that indicate the significant relationship between spatial heterogeneity and property price (Nappi-Choulet and Maury 2009;Helbich et al 2013;Sipan et al 2018). Therefore, the incorporation of geocoded locations in the price index model could resolve the issue of geographical differences in property price movement at the local level.…”
Section: Methodsmentioning
confidence: 99%
“…This has facilitated the availability of crucial market information to stakeholders such as planners and property developers and other policy makers in the property industry (Hacievliyagil et al , 2022). Many of these studies have taken into account proximity and spatial effects (Song et al , 2022; Peng, 2020; Sipan et al , 2018). This is because house prices usually have a relationship to spatial issues (Ismail et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is no developed house price index, although recent research has shown that the market is not random and that there is a possibility to have such an index in place (Nyanda and Muyingo, 2023). Because of the relative importance of proximity and spatial effects to house prices (Ismail et al , 2021; Sipan et al , 2018), it is best that such effects are tested to decide whether they should or should not be included in the hedonic pricing model, which in this case would be the basis for creating a house price index for Dar es Salaam (Nyanda and Muyingo, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation